2020
DOI: 10.2478/ttj-2020-0021
|View full text |Cite
|
Sign up to set email alerts
|

A Big Data Application for Low Emission Heavy Duty Vehicles

Abstract: Recent advances in green and smart mobility aim to reduce congestion and foster greener, cheaper and with less delay transportation. The reduction of fuel consumption and CO2 emissions have worked on light-duty vehicles. However, the reduction of emissions and consumables without sacrificing on emission standards is an important challenge for heavy-duty vehicles. The paper introduces a big data system architecture that provides an on-demand route optimization service reducing NOx emissions of heavy-duty vehicl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Although in the previous study the dominant topic in the field of logistics and transportation were intelligent transportation systems (ITS), in recent years, logistics planning has gained slightly more prominence. Routing optimization (Dimokas et al, 2020;Wiegmans et al, 2020) and traffic monitoring (Ibrahim et al, 2020;Hwang, 2021;George & Santra, 2020; prevail in the ITS domain. In addition, process traceability (Yineng Harrison et al, 2020) is a newly emerged topic in literature in this context.…”
Section: In What Areas Of Scm Is Da Being Applied?mentioning
confidence: 99%
“…Although in the previous study the dominant topic in the field of logistics and transportation were intelligent transportation systems (ITS), in recent years, logistics planning has gained slightly more prominence. Routing optimization (Dimokas et al, 2020;Wiegmans et al, 2020) and traffic monitoring (Ibrahim et al, 2020;Hwang, 2021;George & Santra, 2020; prevail in the ITS domain. In addition, process traceability (Yineng Harrison et al, 2020) is a newly emerged topic in literature in this context.…”
Section: In What Areas Of Scm Is Da Being Applied?mentioning
confidence: 99%
“…An analysis of these collected data revealed that the map of annual weekly NO, NO 2 , and black carbon results had a steeply persistent pattern of contamination of up to 5 to 8 times. The authors of [37] proposed a system that recommends routes and vehicle speeds that minimize NOx emissions and use on-demand route optimization. Finally, In [38], a spatial econometric model was used to study the impact of smart transportation on CO 2 emissions in China.…”
Section: Predict and Minimize Transportation Emissionsmentioning
confidence: 99%
“…Data-driven solutions in the form of data collection and analysis and also in the form of predictive analytics to anticipate traffic congestion, optimize public transportation schedules, and improve the efficiency of transportation networks [77,78].…”
Section: P17mentioning
confidence: 99%